Progesterone Aggravates Lung Fibrosis in a Mouse Model of Systemic Sclerosis - Vafashoar, Fatemeh; Mousavizadeh, Kazem; Poormoghim, Hadi; Haghighi, Amir; Pashangzadeh, Salar; Mojtabavi, Nazanin (Frontiers in Immunology, 2021)
Background: Gender-related factors have explained the higher prevalence of autoimmune diseases in women. Sex hormones play a key role in the immune system and parenchymal cells function; therefore, these hormones can be important in the pathogenesis of autoimmune diseases as a risk or beneficial factor. Lung fibrosis is the main cause of mortality in systemic sclerosis, a female predominant autoimmune disease. The objective of this study was to examine the effect of progesterone on molecular mechanisms of lung fibrosis in a mouse model of systemic sclerosis. Methods: Mice with bleomycin-induced lung fibrosis treated with progesterone subcutaneously for 21 and 28 days. Blood was collected for hormone and cytokine measurement at the end of treatment then, skin and lung tissues were harvested for histological assessment, gene expression, cytokine, hydroxyproline, and gelatinase measurement. Results: Trichrome staining and hydroxyproline measurements showed that progesterone treatment increased the content of collagen in fibrotic and normal lung tissues. Progesterone increased α-SMA (P < 0.01), TGF- β (P < 0.05) and decreased MMP9 (P < 0.05) in fibrotic lung tissues. Also progesterone treatment decreased the gene expression of COL1A2 (P <0.05), CTGF (P <01), ET-1(0.001) in bleomycin- injured lung tissues. The serum level of TNF-α was decreased, but the serum level of cortisol was increased by progesterone treatment in fibrotic mice (P< 0.05). Conclusion: Our results showed that progesterone aggravates lung fibrosis in a mouse model of systemic sclerosis.